2000
DOI: 10.1111/j.1469-7793.2000.t01-1-00669.x
|View full text |Cite
|
Sign up to set email alerts
|

Voltage‐independent calcium entry in hypoxic pulmonary vasoconstriction of intrapulmonary arteries of the rat

Abstract: It has been proposed that hypoxic pulmonary vasoconstriction (HPV) is mediated via K+ channel inhibition and Ca2+ influx through voltage‐gated channels. HPV depends strongly on the degree of preconstriction, and we therefore examined the effect of Ca2+ channel blockade on tension and intracellular [Ca2+] ([Ca2+]i) during HPV in rat intrapulmonary arteries (IPAs), whilst maintaining preconstriction constant. We also investigated the role of intracellular Ca2+ stores. HPV demonstrated a transient constriction (p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

18
181
4
5

Year Published

2001
2001
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 160 publications
(209 citation statements)
references
References 48 publications
18
181
4
5
Order By: Relevance
“…9). This may in turn promote calcium influx because of the subsequent activation of the store refilling current (43). These findings (43) and our own (11), do not support the view (2-8) that phase 1 of HPV in isolated vessels is mediated by Ca 2ϩ influx through voltage-gated Ca 2ϩ channels.…”
Section: Discussioncontrasting
confidence: 52%
See 1 more Smart Citation
“…9). This may in turn promote calcium influx because of the subsequent activation of the store refilling current (43). These findings (43) and our own (11), do not support the view (2-8) that phase 1 of HPV in isolated vessels is mediated by Ca 2ϩ influx through voltage-gated Ca 2ϩ channels.…”
Section: Discussioncontrasting
confidence: 52%
“…Recent investigations have suggested that phase 1 of HPV may result from an initial fall in ATP levels and inhibition of the SR Ca 2ϩ ATPase, leading to an increase in the net efflux of Ca 2ϩ from the SR (Ref. 43 and Fig. 9).…”
Section: Discussionmentioning
confidence: 99%
“…Hypoxia causes intracellular Ca 2+ increase, reaching maximum level in 1-2 min, and this is sustained during hypoxia, reversing on return to normoxia (Robertson et al, 2000). Urena et al (1996) found that in conduit pulmonary artery smooth muscle cell, hypoxia reduced basal intracellular Ca 2+ and decreased Ca 2+ spikes (Urena et al, 1996), consistent with the lack of significant HPV in conduit pulmonary arteries (Archer et al, 1996).…”
Section: Potassium Channelssupporting
confidence: 64%
“…Calcium accumulation occurs by release from intracellular stores such as the sarcoplasmic reticulum or influx through voltage-dependent channels. Investigators have shown that blocking calcium channels (2,10,22), depletion of intracellular calcium stores (6,8,9,22), and removing extracellular calcium (10, 13) inhibit hypoxic contraction, whereas calcium agonists potentiate HPV (24). Thus we speculate that the downstream events in PKC activation during hypoxia involve calcium influx and subsequent smooth muscle contraction.…”
Section: Discussionmentioning
confidence: 99%